Aplicación de un índice para la evaluación de la sustentabilidad de Sistemas de Saneamiento Rural en Leimebamba-Amazonas - Fujishima Martell, Hugo (2022)
The rural water and sanitation systems are administered by district municipalities and community organizations, but the service provided by most of these systems has not been efficient, since the drinking water they offer is not healthy, safe, continuous, or fully social access, solid waste is not properly disposed of, wastewater is not treated and the natural sources that provide this service are not protected, so the comprehensive sustainability of these systems is not assured. The national norm establishes that in rural areas the district municipalities are in charge of providing water and sanitation services to the population in their jurisdiction, directly through the municipal management units (UGM) and indirectly through of community organizations such as the administrative boards of sanitation services (JASS), to which the municipality entrusts the responsibility but must provide them with technical assistance, training and supervision so that they can perform the service well. The district municipality of Leimebamba, in the province of Chachapoyas, department of Amazonas, is a local government in rural areas that is in charge of technical assistance, training and supervision of water and sanitation services provided by all seven communitarian organizations recognized as JASS by the mayor authority. The fulfilment of these municipal functions requires that the municipality has a set of capacities, resources, instruments, equipment and materials that allow it to assist, monitor and evaluate the integral and sustainable management that the JASS must develop during the provision of water services. and sanitation in their communities. An essential element to fulfil this guiding role is to have an instrument to periodically assess whether the management carried out by the JASS is implemented in a comprehensive and sustainable manner. To this end, this ongoing research is experimentally developing, together with the Municipal Technical Assistance Office (ATM) of Leimebamba, an index for evaluating the sustainability of rural sanitation systems in the district. This index considers the social, economic, environmental, technical and institutional dimensions as the most important aspects to assess the comprehensiveness and sustainability of rural sanitation systems, identifying in each of these dimensions the key factors and indicators to be taken into account. The index was subjected to expert judgment by 3 specialists using a Linkert scale to assess the clarity, coherence and relevance of the indicators. The values ​​found in each allowed a selection of indicators, choosing 77 according to the experts' assessments. Likewise, the values ​​obtained indicate that the index allows estimating the comprehensiveness and sustainability of rural sanitation systems. A first experimental application of this index has been carried out in the 2 main JASS of Leimebamba, the JASS Palmira that serves 512 residents and the JASS Dos de Mayo that serves 912, which together serve 75% of the rural population served. by JASS, the main reason why these two community organizations were selected as subjects of the experimental application. For this first application of the instrument, the index was compared with the information provided by the regional supervisory entity, SUNASS Amazonas in its supervision reports, and with the information obtained in the interviews held with the leaders of both JASS and the responsible municipal official. from the ATM office. The results of the application indicated that the sustainability levels of both JASS are at the stable level.